First Language Transfer and Its Role in English Learning among Secondary School Students: Evidence from a Multilingual Region of Indonesia - Hilda Rakerda; Arry Desta Yudriyan; Ahmad Fahrezi; Heber Farel Ericson Gultom; Rina Suryani (Journal of English Language Proficiency, 2026)
This study examines the role of first language transfer in English learning among secondary school students in the multilingual context of Bangka Belitung, Indonesia. It responds to continuing debate over whether first language use hinders or supports second language development. Using a qualitative case study design, the research draws on semi-structured interviews with one teacher and ten students from a senior high school in Bangka Island who had participated in an English drama competition and demonstrated strong spoken English ability. The study is interpreted through pedagogical translanguaging, supported by the concepts of languaging and plurilingual pedagogy, which together frame learners’ first language as a valuable cognitive and communicative resource. The findings show that first language transfer facilitates comprehension, idea development, confidence, and negotiation of meaning rather than functioning solely as interference. A notable finding is the bridge-and-reformulate pattern, in which learners use their first language as a transitional step before producing English utterances in classroom interaction.